Genomic sequences of HLA‐A*68:169, HLA‐B*07:298 and HLA‐B*39:129. (8th March 2018) - Balas, A.; Planelles, D.; Rodríguez‐Cebriá, M.; Puig, N.; Vicario, J. L.
Summary: Three new HLA class I alleles were described in the Spanish population. HLA‐A*68:169 and ‐B*39:129 show one amino acid replacement at the α1‐domain, compared to A*68:02 (P47 > L47) and ‐B*39:06 (S11 > A11), respectively. HLA‐B*07:298 presents one nucleotide mutation within exon 1, resulting in a new amino acid position −14, L>Q, which has not been previously described in any HLA protein. Prediction of the B*07:298 signal peptide cleavage did not show significant differences in comparison with that obtained for the rest of HLA‐B genes.